A Material World: A Comparative Study of Flooring Material Influence on Patient Safety, Satisfaction, and Quality of Care. Issue 1 (March 2017) - Harris, Debra
The purpose of this multi–method study was to compare indoor environmental quality (IEQ) of patient rooms and the effects on safety, satisfaction, and quality of care. Objective analysis of IEQ included temperature, relative humidity (RH), CO2, and TVOCs. Healthcare staff and patients were asked to complete surveys. A behavior mapping study focused on length of time healthcare staff and visitors spent with patients in their rooms. All statistical tests were conducted with an α level of .05. Results indicated that IEQ was compromised by low RH and high temperatures; and bacterial counts in the air were higher in rooms with vinyl flooring. Patients were more satisfied with their experience; less likely to be assigned at risk for falling ; and contributed to social support with visitors spending more time with patients in rooms with carpet tile. This comparative study indicates that the indoor environment contributes to quality of care, patient satisfaction, and safety in patient rooms.